Sustainable Company: Examining the Influence of Environmental, Social and Governance in Improving Company Performance - Muhammad Saiful Hakim; Muhammad Haris Jauhari; Ika Safitri (Eduvest - Journal of Universal Studies, 2025)
The growing awareness of sustainability has prompted companies to adopt more responsible and ethical business practices. Consequently, corporate performance is no longer assessed solely based on economic profit but also on how effectively companies mitigate negative environmental and social impacts. In this context, the implementation of environmental, social, and governance (ESG) principles has become a crucial factor influencing corporate performance. However, studies on the relationship between ESG practices and firm performance in emerging markets, particularly in Indonesia, remain limited and inconclusive. Addressing this gap, this study aims to analyze the impact of ESG implementation on the operational performance and market value of companies listed on the Indonesia Stock Exchange (IDX). Using a panel data regression approach with secondary data from IDX-listed companies, the analysis reveals a significant positive relationship between ESG practices and firm performance. Companies that integrate ESG principles tend to exhibit stronger operational outcomes, enhanced investor confidence, and improved market valuation. These findings highlight the importance of ESG adoption not only as a tool for long-term sustainability but also as a strategic advantage that can strengthen competitiveness in a dynamic business environment.